The co-evolution of social networks and selection system orientations as core constituents of institutional logics of future entrepreneurs at school - Ebbers, Joris J.; Wijnberg, Nachoem M. (Journal of Business Venturing, 2019)
In contexts where a choice between competing institutional logics is possible, the social networks of future entrepreneurs affect their adoption of particular logics. Using a panel data method for studying the co-evolution of social networks and individual actor behavior (SIENA), we study how selection system orientations as core constituents of institutional logics affect, and are affected by, social networks. Our empirical setting is a cohort of film school students, whose social network ties and selection system orientations are measured over a period of three years. We find that students with a strong market selection orientation are less popular among their peers at school, and that the market selection orientation of students is influenced through their social network ties with students from the same cohort.